Who Needs Jobs? Spreading Poverty or Increasing Welfare - Lemieux, Pierre. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
In Who Needs Jobs?, Lemieux explains how jobs are not the goal of economic life and how creating jobs should not be the goal of public policy. He delves into how income and prosperity are created (businesses producing what consumers demand), proposes solutions to the unemployment problem, and provides readers with the knowledge to navigate the jobs discussions of politicians and economists in America. With his approach, Lemieux takes this controversial and complex topic and makes it understandable, using economic analysis and real world examples.